Termômetro da sustentabilidade : uma proposta metodológica com aplicação no estado da Paraíba - Abreu, Lucas Araújo (2022)
One of the main challenges related to sustainable development is due to the conciliation of factors, such as population growth, economic development, and environmental preservation. Despite the evolution in awareness and the efforts invested so far, it is observed that there is still a lack of the subject's comprehension, conflicts in decision-making choices, and a lack of understanding of Spatio-temporal variations. Given this, it was suggested, through this study, an index that presents the sustainability level of territories, especially municipalities in Brazilian federative units, entitled Thermometer of Sustainability (TS), having as a case study the 223 cities in the state of Paraíba. Based on an innovative and systemic construction proposal, the TS adopted a methodology consisting of a few steps. First, it ranges from determining the critical points of the system to stakeholders' consultation to verify strengths and weaknesses in the development of an interactive tool, which provides quick and efficient visualization of the results obtained through the index application. It is composed of five levels: critical, alert, moderate, acceptable, and ideal, with scale ranges based on the Municipal Human Development Index (HDI), an index with a global methodology. The results showed that no municipality in Paraíba fits the best classification of the TS - ideal. Moreover, the vast majority is included in the "critical" level, with more than 80% of the locations. Furthermore, the performance of the environmental and economic indexes was lower than the social index. Finally, when performing the sensitivity analysis, it was observed that the founded values suffered minor changes in the regions of Campina Grande, Patos, and Sousa-Cajazeiras (less than 10%) and intermediate changes in the area of João Pessoa (above 15%). It is expected that, with the formulation of the Thermometer of Sustainability, a more solid assessment of regional and local inequalities will be established, providing for the elaboration of specific and directed public policies towards a local development process on sustainable bases.